Post-transcriptional regulation in root development - Stauffer, Eva; Maizel, Alexis (Wiley interdisciplinary reviews. RNA, 2014)
Plants constantly adapt their root system to the changing environmental conditions. This developmental plasticity is underpinned by changes in the profile of the mRNA expressed. Here we review how post-transcriptional modulation of gene expression control root development and growth. In particular we focus on the role of small RNA-mediated post-transcriptional regulation processes. Small RNAs play an important role in fine tuning gene expression during root formation and patterning, development of lateral organs and symbiosis, nutrient homeostasis, and other stress-related responses. We also highlight the impact of alternative splicing on root development and the establishment of symbiotic structures as well as the emerging role of long noncoding RNAs in root physiology. WIREs RNA 2014, 5:679-696. doi: 10.1002/wrna.1239 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.